Synchronization Of Aceh's Revenue And Expenditure Budget Management Planning With Government Policy - Dian Kesuma; Eddy Purnama; M. Jafar (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2026)
Article 170 paragraph (1) of Law Number 1 of 2022 concerning HKPD emphasizes the synchronization of fiscal planning and policy for integrated national development. However, in the APBA (Aceh Provincial Budget) planning, discrepancies persist between the Aceh Government’s documents and the central fiscal policy direction, leading to synchronization that remains administrative rather than substantive. This issue is further complicated by Aceh's special status under Law No. 11 of 2006, which results in differences in macro indicators, program structure, and a lack of substantive participation from Aceh, creating epistemological inequality and structural injustice in central-regional financial relations. The research aims to understand why APBA management planning is not fully synchronized with government policy and to explore the ideal procedure for achieving synchronization, considering Aceh’s unique autonomy. This study is a normative juridical analysis using a legislative, conceptual, historical, and futuristic approach, with the application of authority theory, policy suitability theory, asymmetric decentralization theory, and good governance principles. The findings reveal that the lack of synchronization is caused by procedural issues, such as the absence of integration between RKPD (Regional Government Work Plan) and RKP (National Government Work Plan) schedules, the lack of a mechanism for reducing KEM-PPKF indicators, unclear fiscal support evaluation, and absence of guidelines and sanctions. Additionally, there are substantial issues like the incompatibility of Aceh's macro indicators with national targets. To achieve ideal synchronization, normative legality, equal central and regional authority, and integrated planning systems are needed.